2020
DOI: 10.1002/agj2.20101
|View full text |Cite
|
Sign up to set email alerts
|

Biosolids and biochar application effects on bahiagrass herbage accumulation and nutritive value

Abstract: Pastures represent the major cropping system where biosolids are recycled in Florida, yet limited information is available documenting the agronomic benefits of biosolids recycling programs. A 2-yr experiment evaluated bahiagrass (Paspalum notatum Flügge) responses to application of biosolids and inorganic fertilizer applied either alone or in combination with biochar. Our hypothesis was that biochar could alter soil N and P dynamics, thus, affecting crop nutrient use efficiency. Treatments were a factorial ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
15
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 43 publications
8
15
6
Order By: Relevance
“…The significant drought period experienced in spring 2017 may have limited forage growth during the 2017 growing season. Data from previous published work conducted in the same experimental area confirmed that forage production was 18–21% greater in the 2018 than in the 2017 growing season (Lu et al., 2020). Results obtained in the current study were consistent with previous studies in the region, suggesting greater N offsite transport from agricultural fields mainly occurred during the months of June to October, which coincide with the rainy season in Florida (Zhang et al., 2007).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The significant drought period experienced in spring 2017 may have limited forage growth during the 2017 growing season. Data from previous published work conducted in the same experimental area confirmed that forage production was 18–21% greater in the 2018 than in the 2017 growing season (Lu et al., 2020). Results obtained in the current study were consistent with previous studies in the region, suggesting greater N offsite transport from agricultural fields mainly occurred during the months of June to October, which coincide with the rainy season in Florida (Zhang et al., 2007).…”
Section: Discussionsupporting
confidence: 54%
“…In Florida, biosolids are mainly applied to perennial pastures as an alternative source of nutrients (Florida Department of Environmental Protection, 2013). The agronomic benefits associated with land application of biosolids to pastures such as increased forage production and nutritive value are extensively documented in the scientific literature (Adjei & Rechcigl, 2002; Avery et al., 2018; Cogger, Bary, Myhre, & Fortuna, 2013; Corrêa & Silva, 2016; Lu, Silveira, Vendramini, Erickson, & Li, 2020). However, public concerns regarding the potential impacts of biosolids on water quality have prompted recent revisions in biosolids regulations in Florida, which resulted in a significant reduction in the area where biosolids can be land applied in the state.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is less than compelling for a positive response of plant tissue minerals to biochar application rate. For example, in both contrast and concurrence to mineral responses to biochar application rate in this study, Keith et al, (2016) and Lu et al, (2020) reported no effects of biochar amendment on tissue minerals (N, P, K, S, Ca, Mg, Fe, Mn, Zn and Cu) concentrations of mixed pasture biomass and bahiagrass (Paspalum notatum Flügge), respectively. Further, Lentz and Ippolito (2012) reported no effect of biochar application on corn silage nutrient concentrations in the first year (2009) but in the second year of their study (2010) biochar decreased silage Cu, S and total N concentrations.…”
Section: Forage Tissue Mineral Concentrationssupporting
confidence: 59%
“…Biochar application produces a variable growth response and nutrient composition in perennial forages. For example, Lu et al (2020) found that adding biosolids increased the crude protein content of perennial bahiagrass (Paspalum notatum Flügge) by up to 39% compared to the unamended control. Still, crude protein values of this forage were the same in biochar and inorganic fertilizer-treated plots in their experiment.…”
Section: Plant Responses To Biochar Applicationmentioning
confidence: 99%